Model of Soybean Raw Material Inventory Planning for the Tofu and Tempeh Production Process at Mekar Sari in Kalukku-Mamuju, Indonesia - Putri, Israyani; Aqil, Muhammad; Junaeda , J. (Manunggal Halim Jaya, 2024)
The Soybean Home Industry is a factory that processes soybeans into tofu and tempeh, located in Dipanamba, a village in the Kalukku sub-district of Mamuju Regency. This study aims to analyze the preparation of soybean raw material supply for the tofu and tempeh production process at Mekar Sari in Kalukku District, Mamuju Regency. Using a case study approach, Mekar Sari serves as the primary source of information to meet the research objectives. The data processing method combines both quantitative and qualitative descriptive approaches through observation, interviews, and analysis using the Economic Production Quantity (EPQ) model.